The psychological assessment of mental and physical handicaps - Mittler, Peter (Methuen, 1970)
(create) Presents a survey of the field of testing and diagnosis of handicapped children and adults. Chapters by various contributors cover intellectual and personality assessment, psychophysiological techniques, evaluation of psychiatric, subnormal, and geriatric patients, the assessment of children with various handicaps, the design of remedial programs, the construction of individual intelligence tests, and an account of recent experiments with automated testing systems.